The Red Thread : Buddhist Approaches to Sexuality - Faure, Bernard (Book collections on Project MUSE., 2001)
Is there a Buddhist discourse on sex? In this innovative study, Bernard Faure reveals Buddhism's paradoxical attitudes toward sexuality. His remarkably broad range covers the entire geography of this religion, and its long evolution from the time of its founder, Xvkyamuni, to the premodern age. The author's anthropological approach uncovers the inherent discrepancies between the normative teachings of Buddhism and what its followers practice. Framing his discussion on some of the most prominent Western thinkers of sexuality--Georges Bataille and Michel Foucault--Faure draws from different reser.